Numerical Simulation of Anchor Pullout and Shear Tests Using a Regularized Damage Model - Matthieu Le Noir de Carlan; Ludovic Jason; Luc Davenne (Applied Sciences)
The prediction of the mechanical behavior of anchorage plates in reinforced concrete is crucial for ensuring equipment reliability, particularly in sensitive installations. This paper employs finite element analysis to forecast the experimental outcomes of anchor pullout and shear tests. In this article, a regularized damage model is proposed to simulate the effects of loads transmitted to the concrete by the anchor rod. Specifically, a modified Mazars model is introduced, incorporating an “energetic” regularization in both tension and compression. The model is validated for a single anchor rod under tension and subsequently for a complete anchorage system subjected to both tension and shear forces. Various failure modes, such as concrete cone cracking or steel rupture, are accurately represented, alongside the overall anchorage strength. This approach, thus, faithfully reproduces the mechanical behavior of anchorage plates, ensuring equipment robustness under diverse loading conditions.